Employment Consequences of Restrictive Permanent Contracts: Evidence from Spanish Labor Market Reforms - Adriana D. Kugler; Juan F. Jimeno; Virginia Hernanz (Institute for the Study of Labor (IZA), 2003)
Temporary employment contracts allowing unrestricted dismissals were introduced in Spain in 1984 and quickly came to account for most new jobs. As a result, temporary employment increased from around 10% in the mid-eighties to more than 30% in the early nineties. In 1997, however, the Spanish government attempted to reduce the incidence of temporary employment by reducing payroll taxes and dismissal costs for permanent contracts. In this paper, we use individual data from the Spanish Labor Force Survey to estimate the effects of reduced payroll taxes and dismissal costs on the distribution of employment and worker flows. We exploit the fact that recent reforms apply only to certain demographic groups to set up a natural experiment research design that can be used to study the effects of contract regulations. Our results show that the reduction of payroll taxes and dismissal costs increased the employment of young workers on permanent contracts. Results for older workers show insignificant effects. The results suggest a reasonably elastic response of permanent employment to nonwage labor costs for young workers. We also find positive effects on the transitions from unemployment and temporary employment into permanent employment for young and older workers, although the effects for older workers are not always significant. On the other hand, transitions from permanent employment to nonemployment increased only for older men, suggesting that the reform had little effect on dismissals.
Keywords: J23; J32; J38; J63; J65; 330; temporary employment; dismissal costs; payroll taxes; European unemployment; Arbeitsmarktflexibilisierung; Personalzusatzkosten; Kündigungsschutz; Befristeter Arbeitsvertrag; Beschäftigungseffekt; Schätzung; Spanien